A clinico-epidemiological study of dermatoses in pediatric HIV patients in a tertiary care center - Sukumaran Pradeep Nair; Rony Mathew (Wolters Kluwer Medknow Publications, 2016)
Introduction: Cutaneous lesions are very common in pediatric HIV infection, and many of the dermatoses are linked to the underlying levels of CD4 counts. Aims: The primary aim was to study the clinico-epidemiological patterns of dermatoses in pediatric HIV infection, and the secondary aim was to ascertain if any dermatoses is a marker of HIV infection. Materials and Methods: This is a retrospective descriptive, 1-year study. All data regarding the clinico-epidemiological features of pediatric HIV patients in the study period were analyzed. Results: There were 65 patients in this study, comprising 44 males (67.69%) and 21 females (32.31%). The age group 7-12 constituted the maximum number of cases, 35 (53.84%). Parental to child transmission was the most common mode of transmission seen in 54 patients, (83.07%). Cutaneous manifestations were seen in 43 patients (66.15%). Exaggerated insect bite reaction (IBR) was the most common cutaneous manifestation seen in this study accounting for 19 patients (29.23%), with a mean CD4 count in patients in the age group 1-5 being 425 cells/mm3 and 212 cells/mm3 in the age group 6-12. Conclusions: IBR in pediatric HIV infection indicates very low CD4 counts and in the absence of other caused for immunosuppression can be a marker of HIV infection.